Schist buildings in Peso da Régua county - Pinto, Jorge (2018)
Schist stone is a traditional building material applied in the Peso da Régua County. This County is located in the Northeast part of Portugal related to the Douro region which is UNESCO World Heritage. Dwellings, earth retaining walls and fencings are the most common constructions built with this type of material. They are vernacular constructions which are very well integrated in the local landscape and its maintenance is important to perform. Thus, a set of building details concerning schist dwelling was surveyed in this research work. This paper intends to disseminate the obtained information, in particular, some structural buildings details. In the structural context, schist masonry walls are the main vertical structural elements. Taking into account that the size, the existence of openings (e.g. window or door), the type of corner and the type of lintel of the openings are some building aspects which may influence the structural behaviour of a traditional masonry schist wall, they are highlighted. We believe that this technical information may give some guidance in future studies focused on modelling (numerically and experimentally) the structural behaviour of this type of traditional building element.